2006
DOI: 10.1007/s10067-006-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of soluble Fas (APO-1, CD95), soluble Fas ligand, and matrix metalloproteinase-3 in sera from patients with active untreated adult onset Still’s disease

Abstract: To investigate serum levels of soluble Fas (sFas), soluble Fas ligand (sFas-L), and matrix metalloproteinase-3 (MMP-3) in patients with active untreated adult onset Still's disease (AOSD). Serum levels of sFas, sFas-L, and MMP-3 were determined by enzyme-linked immunosorbent assays in 20 patients with active untreated AOSD, 20 patients with active rheumatoid arthritis (RA), and 20 healthy controls. Linear regression was used to evaluate the correlation between clinical activity scores and serum levels of sFas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This hypothesis is also supported by raised Fas and FasL levels in untreated AOSD patients compared to healthy controls [50]. …”
Section: Pathophysiologymentioning
confidence: 88%
“…This hypothesis is also supported by raised Fas and FasL levels in untreated AOSD patients compared to healthy controls [50]. …”
Section: Pathophysiologymentioning
confidence: 88%
“…Globally, the illness primarily affects young adults (the median age at diagnosis is approximately 36 years) [ 7 , 8 ]; but cases have been reported as late as 83 years [ 9 , 10 ]. While the exact cause of AOSD remains unknown, researchers have identified elevated levels of certain inflammatory markers, including tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-18 (IL-18), in individuals with the condition [ 5 ]. These elevated markers are believed to contribute to the systemic inflammation seen in AOSD.…”
Section: Discussionmentioning
confidence: 99%
“…While no specific diagnostic laboratory test exists, serum ferritin levels can aid in monitoring and considering AOSD [ 4 ]. Treatment primarily consists of non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and rheumatological agents [ 5 ]. Negative antinuclear antibody (ANA) and Rheumatoid (RA) factor are included as part of the minor criteria for diagnosing AOSD; however, rare cases with positive ANA and no other features of systemic lupus erythematosus (SLE) or other autoimmune disorders have been reported, suggesting that a positive ANA or RA factor does not rule out the diagnosis of AOSD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis in patients with autoimmune disease is considered an essential mechanism to counterbalance the abnormal immune response and to maintain immunologic tolerance (5,6). Although cell proliferation is exaggerated in the synovial membrane of patients with RA, studies have shown increased levels of synovial and serum Fas and FasL in these patients likely due to the enhanced inflammatory and oxidative burden on infiltrating mononuclear cells and circulating T lymphocytes (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%